2006
DOI: 10.1002/anie.200601108
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Micelles from Oligopeptide‐Grafted Cyclotriphosphazenes

Abstract: Hard graft: Amphiphilic cyclic phosphazene trimers grafted with hydrophobic oligopeptide (red) and hydrophilic methoxypolyethylene glycol (blue) show a variety of thermoresponsive properties including lower critical solution temperatures near body temperature. They form strong micelles in aqueous solution at an appropriate hydrophobic‐to‐hydrophilic balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…The platinum(II) intermediates, cis-(CHA) 2 Pt(NO 3 ) 2 and cis-(CHA)(NH 3 )PtSO 4 , were prepared according to the literature methods [21,22]. The amphiphilic cyclotrophosphazene drug carriers, [NP(PEG550)(GlyPheLeuAspEt 2 )] 3 and [NP(PEG350)(GlyPheLeuMalEt 2 )] 3 were prepared following the procedure described in our previous work [19,20]. Tetrahydrofuran (THF) was dried by boiling at reflux over sodium metal and benzophenone and then distilled under argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The platinum(II) intermediates, cis-(CHA) 2 Pt(NO 3 ) 2 and cis-(CHA)(NH 3 )PtSO 4 , were prepared according to the literature methods [21,22]. The amphiphilic cyclotrophosphazene drug carriers, [NP(PEG550)(GlyPheLeuAspEt 2 )] 3 and [NP(PEG350)(GlyPheLeuMalEt 2 )] 3 were prepared following the procedure described in our previous work [19,20]. Tetrahydrofuran (THF) was dried by boiling at reflux over sodium metal and benzophenone and then distilled under argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…2 shows that platination results in broadening of the phosphorus resonance of the carrier probably due to molecular aggregations as just mentioned above. In our previous work [19], we have shown that the carrier cyclotriphosphazene molecules do not form micelles but exist as unimer in aqueous solution because of too high hydrophilicity of MPEG550 compared with the hydrophobicity of the tetrapeptide. However, it was found in the present study that platination of the same tetrapeptide with very hydrophobic dicyclohexyl platinum(II) moiety gave rise to strong molecular aggregations.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15] We have demonstrated in our previous study that these tripodal amphiphiles provide strong intra-and intermolecular hydrophobic interactions tunable for self-assembly to various nanostructures such as micelles, bilayered polymersomes, and molecular gels that are ruled by the hydrophobicity parameter (log P) of the oligopeptides employed. In particular, we have shown that the tripodal cyclotriphosphazenes bearing linear oligopeptides with high hydrophobicity (Log P > 1) remain as stable micelles in aqueous solution but those with intermediate hydrophobicity (0 < log P < 1) reassemble into bilayered polymersomes.…”
Section: Introductionmentioning
confidence: 99%